1992
DOI: 10.1091/mbc.3.12.1353
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a tyrosine localization signal in the cytosolic tail of yeast Kex2 protease disrupts Golgi retention and results in default transport to the vacuole.

Abstract: Kex2 protease processes pro-alpha-factor in a late Golgi compartment in Saccharomyces cerevisiae. The first approximately 30 residues of the 115 amino acid CO2H-terminal cytosolic tail (C-tail) of the Kex2 protein (Kex2p) contain a Golgi retention signal that resembles coated-pit localization signals in mammalian cell surface receptors. Mutation of one (Tyr713) of two tyrosine residues in the C-tail or deletion of sequences adjacent to Tyr713 results in loss of normal Golgi localization. Surprisingly, loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
278
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(297 citation statements)
references
References 71 publications
(98 reference statements)
18
278
1
Order By: Relevance
“…The localization of a number of resident late Golgi proteins also depends on recycling from the prevacuolar compartment, and a failure to recycle results in transport to the vacuole, where they are degraded (Wilcox et al, 1992;Nothwehr et al, 1993;Cooper and Stevens, 1996). A-ALP is a model late Golgi protein that consists of the membrane and lumenal domains of ALP fused to the cytoplasmic domain of DPAP A, which contains the sorting information required for localization of the chimera to the late Golgi (Nothwehr et al, 1993).…”
Section: Late Golgi Membrane Proteins Are Destabilized In Vps52 Vps5mentioning
confidence: 99%
“…The localization of a number of resident late Golgi proteins also depends on recycling from the prevacuolar compartment, and a failure to recycle results in transport to the vacuole, where they are degraded (Wilcox et al, 1992;Nothwehr et al, 1993;Cooper and Stevens, 1996). A-ALP is a model late Golgi protein that consists of the membrane and lumenal domains of ALP fused to the cytoplasmic domain of DPAP A, which contains the sorting information required for localization of the chimera to the late Golgi (Nothwehr et al, 1993).…”
Section: Late Golgi Membrane Proteins Are Destabilized In Vps52 Vps5mentioning
confidence: 99%
“…In addition, some Tyr motifs have been found to be important for the retention of membrane proteins at the TGN in mammalian and yeast cells (Bos et al, 1993;Voorhees et al, 1995;Wilcox et al, 1992), and, most recently, a Tyr-based targeting signal has been shown to mediate the sorting of an integral membrane glycoprotein into Golgi-derived CCVs (Honing et al, 1996). These cytoplasmic Tyr motifs interact with other components of the sorting machinery, such as the clathrin-associated AP1 adaptor protein complex (Pladaptin,~1 ,and ul) at the TGN.…”
Section: Dlscusslonmentioning
confidence: 99%
“…Some membrane proteins are trafficked to the lysosome or vacuole by vesicular transport (Wilcox et al, 1992;Berkower et al, 1994). In contrast, the destruction of certain endoplasmic reticulum (ER) proteins, such as the CFTR protein, the unassembled T-cell receptor subunits, and 3-hydroxy-3-methylglutaryl-CoA (HMG-R), appears to occur in situ in the ER without the need for traffic to a degradative compartment.…”
Section: Introductionmentioning
confidence: 99%